Testing method and distribution characteristics of spatial pesticide spraying deposition quality balance for unmanned aerial vehicle - Wang, Changling; He, Xiongkui; Wang, Xiaonan; Wang, Zhichong; Wang, Shilin; Li, Longlong; Bonds, Jane; Herbst, Andreas; Wang, Zhiguo (International Journal of Agricultural and Biological Engineering, 2018)
In order to explore the spatial pesticide spraying deposition distribution, the downwash flow field characteristics for unmanned aerial vehicle (UAV) pesticide application with accurate flight height and velocity and the relationship of these two aspects, a novel measurement method was proposed in this paper. A model ‘3WQF80-10’ single-rotor diesel UAV was tested using this method in wheat field and the effects of flight direction, flight parameters and crosswind on the distribution of spatial spraying deposition quality balance (SSDQB) and the downwash flow field distribution were researched. A cuboid aluminum sampling frame of spatial spraying deposition quality balance (SFSSDQB) with monofilament wires was made for collecting the droplets in four directions, and a set of multi-channel micro-meteorology measurement system (MMMS) was applied for measuring the downwash wind speed in three directions. Besides, BeiDou Navigation Satellite System (BNSS) was used for controlling and recording the working height, velocity and track of this model of single-rotor UAV. The results showed the distribution of the spatial spray deposition and the downwash flow field of UAV could be measured effectively at exact flight height and velocity via this method. When the average wind speed was 0.9 m/s, the average temperature was 31.5°C and the average relative humidity was 34.1%, and the average distribution ratios of spraying deposition for model ‘3WQF80-10’ UAV on the upwind part, the top part, the downwind part and the bottom part were 4.4%, 2.3%, 50.4% and 43.7%, respectively. The flight directions of forward and backward had an impact on droplet deposition distribution and the working effect of flying backwards, with 60% of deposition ratio of the bottom part of the SFSSDQB, was better than flying forward. There was a linear negative correlation between the coefficient of variation (CV) of the bottom part and the flight height and the coefficient of determination was 0.9178, which means that the deposition distribution becomes more uniform with the increase of height. Additionally, there was a linear positive correlation between weighted mean deposition rate and crosswind speed and the coefficient of determination was 0.9684, which shows the deposition distribution gets more concentrated towards the downwind part with the rise of crosswind speed. Therefore, according to the results of tests of downwash airflow speed, it is shown that regardless of the flight direction and height and the crosswind, all these factors influence the droplet deposition distribution via weakening the intensity of the downwash airflow field in the direction perpendicular to the ground. The results can provide valuable information for the research of UAV pesticide application techniques and the establishment of the standard of spraying deposition and drift tests of UAV in crop field. Keywords: unmanned aerial vehicle (UAV), spatial spraying deposition, distribution, downwind airflow, flow field DOI: 10.25165/j.ijabe.20181102.3187 Citation: Wang C L, He X K, Wang X N, Wang Z C, Wang S L, Li L L, et al. Testing method and distribution characteristics of spatial pesticide spraying deposition quality balance for unmanned aerial vehicle. Int J Agric & Biol Eng, 2018; 11(2): 18–26.